2002
DOI: 10.1007/s00467-002-0954-7
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of renal vein renin studies in hypertensive children: a 25-year experience

Abstract: Lateralised renin secretion predicts improvement following surgery/angioplasty of the affected kidney in paediatric hypertension. We retrospectively analysed all our renal vein renin (RVR) studies undertaken in hypertensive children and their subsequent clinical outcomes over a 25-year period. The outcomes were categorised as cure, improvement or no change in hypertension. The proportions that benefited by 'following' or 'ignoring' the RVR results in relation to the aetiology of hypertension and subsequent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Other specific diagnostic procedures are also available to investigate affected individuals [44,47], but experience in their use in children is limited. Nonimaging tests include measurement of peripheral plasma renin activity [48], the captopril test [49] and renal vein renin sampling [50], all of which have inherent limitations. ACE inhibition renal scintigraphy has been proven to be a useful initial screening test [51,52].…”
Section: Etiological Classification Of Elevated Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…Other specific diagnostic procedures are also available to investigate affected individuals [44,47], but experience in their use in children is limited. Nonimaging tests include measurement of peripheral plasma renin activity [48], the captopril test [49] and renal vein renin sampling [50], all of which have inherent limitations. ACE inhibition renal scintigraphy has been proven to be a useful initial screening test [51,52].…”
Section: Etiological Classification Of Elevated Bpmentioning
confidence: 99%
“…They include MR angiography [53], spiral CT scan angiography [54], renal vein renin studies [50], renal angiography [55], MIBG scanning [62], venous catecholamine sampling, somatostatin receptor imaging by 111 In-octreotide scan [62], cerebral isotope scan, cerebral angiography and newer molecular genetic studies for identifying genetic syndromes [63].…”
Section: Advanced Investigations In the Child With Hypertensionmentioning
confidence: 99%
“…On the contrary and more recently, an RVRR of at least 1.55 was found to be useful in identifying patients with RAS more than 70% who benefit from revascularization, while a ratio greater than 1.72 was found to be associated with good outcomes from nephrectomy when renal artery occlusion was present [8]. Other studies also found that lateralization of renin secretion normalized after revascularization [42], that a negative RVRR was predictive of absence of improvement [43] and RVRs were useful in assessing children with RAS [44].…”
Section: Discussionmentioning
confidence: 89%
“…However, it may be difficult to distinguish arteriovenous fistula from aneurysm at color Doppler US, and flow in normal vessels grouped in the renal hilum obscures lighter-colored flow in a small central renal AVF. Although other diagnostic imaging tools might be helpful, angiography remains the standard of reference for confirming or excluding the existence of renal AVF, and selective segmental renal vein renin sampling is invaluable for locating the renin producing lesion 6-8)…”
Section: Discussionmentioning
confidence: 99%